Developing Learning Tools with Cooperative Learning Model of Numbered Head Together (NHT) Structural Approach on Sequence and Series Material - Rahman, Mia Riani; Murni, Atma; Zulkarnain, Zulkarnain (FKIP-Universitas Riau, 2021)
This research was underlined by the few availability of Mathematics learning tools as the teacher’s guidance in implementing the learning and the low Mathematics achievement of the students. This research aims to produce valid, practical, and effective learning tools by using cooperative learning models of Numbered Head Together (NHT) structural approach on sequence and series material. This research and development was conducted by adapting a 4-D development model by Thiagarajan. The stages of this research consisted of Define, Design, Development, and Dissemination. The validation results of the learning tools consisting of syllabus, Lesson Plan, and LKPD that are 92%, 92,07%, and 94,33% with extremely valid criteria. The practicality result on small group trial is 93,99%, big group trial is 93,42% and teacher’s response 93,88% with extremely practical criteria. The effectiveness result shows that the students’ learning achievement increases by using the developed learning tools.